Seabed geomorphology of the Porcupine Bank, West of Ireland. Issue 5 (19th October 2016) - Thébaudeau, Benjamin; Monteys, Xavier; McCarron, Stephen; O'Toole, Ronan; Caloca, Silvia
ABSTRACT: A new map of the seabed geomorphology on the Porcupine Bank, located at the western edge of the north-eastern Atlantic shelf west of Ireland, uses high-resolution multibeam bathymetric and backscatter data as well as numerous shallow seismic profiles to identify individual landforms. They are described based on their acoustic signature on the various datasets. The landforms comprise sharp-crested ridges, mounds and outcrops often associated with and expressing underlying bedrock topography; sand waves highlighting modern currents directions; and iceberg scours with strongly preferred orientations. The map is intended as baseline evidence to test models of the palaeoceanographic and palaeoglaciological history of the Porcupine Bank.